SISTEM KEAMANAN PINTU PAGAR MENGGUNAKAN FINGERPRINT DAN ALARM SEBAGAI PENGAMAN DENGAN NOTIFIKASI TELEGRAM BERBASIS INTERNET OF THINGS (IOT) - Arini Selti Lestari , Widya; Zein Vitadiar , Tanhella (Inovate, 2024)
Currently there are very many criminal cases such as theft so that the security system is the most important thing for every human being, for example a home security system. Currently, home security only uses manual house keys, making it easier for unscrupulous individuals to commit crimes, so a more secure security system is needed to maintain a higher level of security. The existence of this technological development introduces innovations and solutions to create a sophisticated security system tool, one of which is Fingerprint. This fingerprint is implemented as a key replacement tool, so that owners are more efficient in their use. This research produced a security system tool using fingerprints and alarms, the results of this test are that if the finger has been registered, the gate will open automatically and close again after 10 seconds, if the finger has not been registered, the door will not open, and if the door is forced open, an alarm will sound, besides that information about what is happening at the gate can be seen from the Telegram application and can also access the gate from the Telegram application. Key word : Scurity System Fingerprint, Research And Development (R&D)